The Making of the Sin of Achan (Joshua 7) - Berman, Joshua (Biblical interpretation, 2014)
The ascription of blame to an entire people for the infraction of a nondescript individual found in the account of the sin of Achan (Joshua 7) is without parallel in the Hebrew Bible and in the legal and treaty literature of the ancient Near East. Attempts to explain the account through concepts such as “corporate personality” or the “contagion” to be found in devoted goods have rightly come under great scrutiny. This paper seeks to understand collective punishment in Joshua 7 by engaging in a close reading of the final form of the text and with recourse to notions found in contemporary ethical theory. The paper introduces the rhetorical use of minor characters as markers of collective attitudes in biblical narrative. Central to the exposition of the Achan account is the role of the spies’ report (7:2-3) as such a marker of collective attitudes shared by the polity as a whole.